Metformin or insulin: logical treatment in women with gestational diabetes in the Middle East, our experience - Sindu J. Christian; Vincent Boama; Hiba Satti; Joohi Ramawat; Tarik A. Elhadd; Khaled Ashawesh; Khaled Dukhan; Stephen Beer (BMC Research Notes, 2018)
Abstract Objective The debate still continues about the preferred modality of treatment of gestational diabetes requiring pharmacological treatment. Insulin was previously considered as the gold standard, but the National Institute of Health and Care Excellence now recommend metformin as the first line drug of choice. The pharmacological management of gestational diabetes mellitus in the Middle East with its high risk population has not been widely published. We aim to evaluate the safety and efficacy of using metformin in comparison to insulin, in our group of patients, and to study key associated morbidities. Results A total of 291 women registered in the clinic during the study period. One hundred and twenty-one (121) were women with gestational diabetes Mellitus requiring medical therapy. Among them, 107 delivered at term. Ninety (84%) women received metformin. Additional insulin was required in 32% of these patients. There was a significant difference in the birth weight of babies in the metformin with insulin group of 207 g (p value 0.04) in favour of metformin. There was no significant difference in maternal or neonatal morbidities between the groups. Metformin was thus found to be a safe, practical and cost effective medication to be offered to our population.